1993
DOI: 10.1080/08886504.1993.10782088
|View full text |Cite
|
Sign up to set email alerts
|

Computers and Teachers

Abstract: This study examined :he predictiveness of several personal variables of elementary school teachers to their use of available computers for teaching (N = 170 ). Teachers from four schools completed questicnnaires that assessed for three levels of computer use, innovativene~s, teacher locus of control, perceived relevance of computers to teaching, and self-confide.n:;e in the use of compAtters. Additionally, data on age, gender, and years of computer experie.n:::e were collected. Logist&c regression procedures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Related studies showed that there are a vast number of beliefs that using the technology in education will bring about reform. In fact, it was observed that technology was not being used adequately and the current education system could not be integrated with technology in the learning environment (Marcinkiewicz, 1994;OTA, 1995;Cuban, 2001;Monaghan, 2004;Koçak-Usluel, Kuşkaya-Mumcu & Demiraslan, 2007;Author, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Related studies showed that there are a vast number of beliefs that using the technology in education will bring about reform. In fact, it was observed that technology was not being used adequately and the current education system could not be integrated with technology in the learning environment (Marcinkiewicz, 1994;OTA, 1995;Cuban, 2001;Monaghan, 2004;Koçak-Usluel, Kuşkaya-Mumcu & Demiraslan, 2007;Author, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The statistically significant pre- to post-test increase observed in the answers to this question among the experimental group students is likely due to the unique opportunity created by this study for them to join bioinformatics laboratories ( Table 1 ). Recent studies reported that although schools apparently have the necessary conditions to successfully integrate Information and Communications Technology (ICT) in the classroom, there are still barriers, such as teachers’ pedagogical beliefs, which prevent the use of computers in classroom settings ( Marcinkiewicz, 1993 ; Ertmer, 2005 ; Sang et al, 2010 ). Interestingly, some informal comments made by the students revealed that their teachers often feel discouraged to use technology in the classroom because they do not feel comfortable with it, which meets the constraints mentioned by the teacher, the majority of whom acknowledged their anxiety regarding the use of technology in this setting ( Machluf and Yarden, 2013 ; Martins et al, 2018c , 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The related literature also suggests that for a successful integration of ICT with education, an agreement between technology and teachers is required (Marcinkiewicz, 1993). From this perspective, ICT assisted project based learning practices can be considered to provide this agreement.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In this context, ICT is very important and necessary for the transformations expected from learning environments, for it provides opportunities for transforming traditional teacher centred practices into student centred environments and also environments for sharing and cooperation (Papanastasiou & Angeli, 2008). Marcinkiewicz (1993) stated that for a successful integration of ICT with education, an agreement between technology and teachers is required. This should start at teacher training process.…”
Section: Introductionmentioning
confidence: 99%